Structural and Optical Characteristics of Antimony Selenosulfide Thin Films Prepared by Two-Step Method - Türkoğlu, Fulya; Ekren, Memduh Emirhan; Özyüzer, Lütfi; Cantaş, Ayten; Yakıncı, Kübra; Aygün, Gülnur; Gündoğan, Hazal; Aygün, Gülnur; Özyüzer, Lütfi (Springer, 2022)
Antimony triselenide (Sb2Se3) is one of the most promising absorber material choices among the inorganic semiconductors that has attracted much attention today. However, highest recorded efficiencies for Sb2Se3 solar cells are still lower than ideal. Exploring antimony selenosulfide (Sb-2(SxSe1-x)(3)) to increase device performance is one option because some features of alloyed Sb-2(SxSe1-x)(3) depend on composition such as bandgap and band position. In this study, two-step process was used to grow Sb-2(SxSe1-x)(3) thin films. In the first stage, Sb2Se3 thin films were deposited on soda lime glass substrates using direct current magnetron sputtering technique. In the second stage, Sb2Se3 thin films were exposed to sulfurization process in a quartz ampoule to obtain Sb-2(SxSe1-x)(3) thin films. Characterization results showed that morphological, optical, and structural properties of Sb-2(SxSe1-x)(3) thin films grown by presented method were highly dependent on amount of sulfur in the films. By the adjustment of the S/S + Se atomic ratio, Sb-2(SxSe1-x)(3) absorber materials with suitable bandgap, favorable orientation and compact morphology can be obtained for photovoltaic applications.
Keywords: Antimony selenosulfide; Magnetron sputtering; Thin film solar cells